Ogniwo Artura Marii Swinarskiego w serii translatorskiej utworów Johanna Wolfganga Goethego - Grodecka, Aneta (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
Based on the findings of translation experts on the translation series, the author focuses on Polish-German tropes in the works of A.M. Swinarski, carrying out a detailed analysis of selected translations of Goethe’s poems. A comparison of translations by Swinarski, Jarosław Iwaszkiewicz, Stefan Zarębski, Feliks Konopka and Andrzej Lam reveals changes in the sphere of meanings designed in the original and reflects on the principles of literality and interpretation in translation practice.